Arbitrating During and Post Covid-19: Nigeria and the Imperativeness of Adopting a Legal Framework on Third-Party Funding: Lessons from Selected Jurisdictions - Eyongndi, David; Opara, Faith N. (Strathmore Law Journal, 2022)
The advent of Covid-19 has led to the inability of parties fulfilling their commercial and contractual obligations. This inability has led to disputes and has negatively affected the financial fortune of many persons and businesses so that they may not afford or solely bear the cost of funding arbitration. To ensure that parties’ intention to arbitrate their disputes is not frustrated, Third-party funding (TPF), an acceptable practice in jurisdictions such as the United Kingdom (UK), Singapore, and Hong Kong, is a possible solution. Unfortunately, TPF is unknown to Nigerian law as it offends the common law doctrines of champerty and maintenance. This article, through a doctrinal methodology, examines the legislative effort towards institutionalising TPF in Nigeria and the ethical concerns advanced against it. The article argues that these concerns are more imaginary than real. Hence, they ought not to deter the adoption of TPF in Nigeria for intra- and post-Covid-19 funding of arbitration. It discusses the practice of TPF in the UK, Hong Kong, Singapore, South Africa, Ghana, and France in which these ethical concerns have been dealt with and draws lessons for Nigeria.